CHARACTERIZATION AND SCREENING PARAMETERS OF SPRAY FILM-FORMING SYSTEMS: A COMPREHENSIVE STUDY ON DOSAGE FORMS AND QUALITY INDICATORS - M. M., SHUMKOVA; E. O., BAKHRUSHINA; M. A., DAVYDOVA; G., POUYA; M. M., AGABALYAN; A., TIMOSHKINA ALEKSANDRA; E. V., NOVOZHILOVA; N. B., DEMINA; I. I., KRASNYUK (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of this study is to present the main screening parameters for the development of Spray Film-Forming Systems (SFFSs) using the design space. The focus is on characterizing the different phase states of SFFSs during application and establishing appropriate methods for determining the range of parameters. Methods: In this study, various methods were used to determine the range of SFFS parameters. These include contact angle determination, pH test, viscosity measurement, drying rate estimation, spray pattern determination, tensile strength test, and washability. The methods used were evaluated and found to be effective in assessing the quality parameters of liquid concentrates, aerosols, and films of commercially available SFFS samples. Results: Three states (liquid, aerosol, and solid) of commercially available SPSFs were evaluated using the techniques mentioned above. The applicability of the techniques and variability was discussed in comparison with similar studies. The results showed that the mean pH ranged from 5.43±0.02 to 6.63±0.05, the bioadhesion of liquid concentrates was in a narrow range of 4.49±0.52, the highest index of dynamic viscosity was 0.33±0.04, values of the spray pattern ranged from 6.19±1.97 to 17.46±2.72 cm2, bioadhesion values of the films ranged from 3.87 to 4.06 N, average values of film formation time were in the range of 65.55±12.65) s. 3 of the 4 samples had resistance to skin cracking, the tensile load of the commercial SFFS films varied from 2.91±0.3 to 5.11±0.65 N, and the tensile strength from 1.07±0.11 to 1.20±0.3 mPa. All films were not washed off with water. Conclusion: The findings of this study demonstrate the successful application of tested methods in determining the range of parameters for SFFSs. The established values for indicators of liquid concentrates can serve as a basis for the further development of SFFSs. Overall, this research contributes to the understanding and standardization of Spray Film-Forming Systems for wounds, enabling their effective development and application in local skin treatments.